Association Between Professional Commitment and Reported Medication Errors in Nurses - Khadijeh Nasiri; Hannaneh Hamidi; Mohaddeseh Hajizadeh; Somayeh Gholinejad; Javad Ebadi; Maryam Mirzaee Jirdehi; Alireza Khateri; Esmaeil Najafi (Journal of Holistic Nursing and Midwifery)
Introduction: Medication error and professional commitment are two topics in the nursing profession. Objective: The current study aims to determine the association between professional commitment and reported medication errors in nurses working in hospitals in Ardabil and Khalkhal cities, Iran, in 2021. Materials and Methods: This descriptive-analytical research was correlational and was conducted on 350 nurses working in educational and medical centers in Ardabil and Khalkhal cities in the north of Iran in 2021. Sampling was done by simple random method. The questionnaire on professional commitment and medication error was used to collect information. The t-test, Pearson test, chi-squared test and multivariate linear regression were used to determine the associations between study variables. Results: The results show that the Mean±SD of the study participants’ age was 34.76±27.20 years and most participants were female (78.28%). Also, the Mean±SD of the total score of medication error and professional commitment in nurses were 14.64±4.56 and 94.15±11.97, respectively. Statistically, there was a significant relationship between medication error and nurses’ professional commitment (P=0.008, r=-0.15). The results show that among the investigated variables and their effect on medication error, commitment to the nursing profession (β=0.154, 95% CI; 0.001%, 0.3%, P=0.048) has a direct and significant relationship, with the increase in commitment to the nursing profession, medication error increases and also married status (β=-0.261, 95% CI; -2.96%, -1.007%, P=0.002) has an indirect and significant relationship with medication error. Conclusion: The study’s findings showed a statistically significant relationship between professional commitment and medication errors in nurses. Therefore, strengthening the organizational commitment of nurses can reduce medication errors and ultimately increase the safety of patients.